Miss Nelson is back - Allard, Harry; Marshall, James (Boston Houghton Mifflin, 1982)
When their teacher has to go away for a week, the kids in room 207 plan to "really act up."
"Sandpiper Houghton Mifflin Books."
Keywords: Schools -- Fiction; Teachers -- Fiction